2019
DOI: 10.5398/tasj.2019.42.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Association of 5’UTR CAPN1 Gene with Growth Traits in Bali Cattle by PCR-RFLP

Abstract: The aim of this study was to identify the variation of 5'UTR CAPN1 gene and its association to growth traits in Bali cattle. DNA samples were obtained from 80 heads of Bali cattle originated from BPTU-HPT Denpasar. The average of Bali cattle age was 784 days (631 days-1098 days). Bali cattle were divided into 3 age groups namely, the first group (1.5 years to 2 years), the second group (2 years to 2.5 years), and the third group (2.5 years to 3 years). The observed growth traits were birth weight (kg), live we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
2
Order By: Relevance
“…Bali cattle with the GG genotype had the highest body weight at 730 days compared to the GT genotype. Sihite et al (2019) showed that the CAPN1 gene was associated with birth weight and average daily gain, which differs from this present study in terms of the number of samples used. These findings suggested that SNP g.232 G>T polymorphisms potentially be used as the candidate of Marker Assisted Selection (MAS) for selection criteria for growth trait.…”
Section: Association Of Genotype With Growth and Meat Quality Traitscontrasting
confidence: 99%
See 1 more Smart Citation
“…Bali cattle with the GG genotype had the highest body weight at 730 days compared to the GT genotype. Sihite et al (2019) showed that the CAPN1 gene was associated with birth weight and average daily gain, which differs from this present study in terms of the number of samples used. These findings suggested that SNP g.232 G>T polymorphisms potentially be used as the candidate of Marker Assisted Selection (MAS) for selection criteria for growth trait.…”
Section: Association Of Genotype With Growth and Meat Quality Traitscontrasting
confidence: 99%
“…However, there was no information about the association of 5'UTR with meat quality in Bali cattle. According to Sihite et al (2019), Bali cattle with the GG genotype have the highest value of live weight and average daily gain than the GT and TT genotypes.…”
Section: Polymorphisms Of Snp G232 G>t 5'utr Regionmentioning
confidence: 99%
“…The result of the association shown that both SNPs and dele-tion mutation in the 3'UTR polymorphism was not associated (P>0.05) with growth traits in Bali cattle (Table 3). This result was different from the 5'UTR polymorphism of CAPN1 by previous studies of Sihite et al, (2019) shown that the CAPN1 gene was associated with live weight and daily body weight gain in Bali cattle. The result from this study was in accordance with previously studied by Pintos and Corva 2011;Café et al, 2010 shown that the CAPN1 gene as the major role of flavoring tenderness was a negative effect on growth traits in Argentinian Angus and Brahman cattle.…”
Section: The Association Of 3'utr Polymorphism With Growth and Meat Q...contrasting
confidence: 97%
“…If the first is large, the allele frequencies are different. Sihite et al (2019) stated that the population of Bali cattle in BPTU-HPT Denpasar has undergone selection, so no located in Hardy-Weinberg equilibrium. A population was in Hardy-Weinberg equilibrium if there was no selection, mutation, migration and genetic drift.…”
Section: Resultsmentioning
confidence: 99%